PENGARUH EKSTRAK METANOL DAUN PEPAYA (Carica papaya L.) TERHADAP AKTIVITAS ENZIM LIPASE - Nurhaeni Nurhaeni; Ahmad Ridhay; Magfira Magfira (KOVALEN: Jurnal Riset Kimia, 2017)
Has conducted research on the effects of methanol extract of leaves papaya (Carica papaya L.) Against Lipase Enzyme Activity. This study aimed to obtain information in a methanol extract inhibits lipase activity. The method used is Complete Random Design (RAL), with goal attainment is done by determining the incubation time lipase enzyme, pH optimum lipase enzyme, and maximum substrate concentration lipase enzyme. And determining the effect of the methanol extract to inhibit the lipase enzyme activity. The results showed that the best incubation time of lipase obtained by time of 120 minutes, the optimum pH 7 and the maximum substrate concentration of 4%. With the highest activity were obtained 16.94 mol /ml.menit, 13.33 mol / ml.menit, and 12.89 mol / ml.menit. The methanol extract of papaya leaves can inhibit the lipase enzyme activity the best concentration of 2% with the acquisition activity of 3.67 mol/ml.menit.Keyword: papaya, lipase, incubation time, optimum pH, substrate concentration.